Comparative genomics reveals cellobiose hydrolysis mechanism of Ruminiclostridium thermocellum M3, a cellulosic saccharification bacterium - Tao, Sheng; Qingbin, Meng; Zhiling, Li; Caiyu, Sun; Lixin, Li; Lilai, Liu (Frontiers in Microbiology, 2023)
The cellulosome of Ruminiclostridium thermocellum was one of the most efficient cellulase systems in nature. However, the product of cellulose degradation by R. thermocellum is cellobiose which lead the feedback inhibition of cellulosome, and limits the R. thermocellum application in the field of cellulosic biomass consolidated bioprocessing (CBP) industry. In previous study, R. thermocellum M3 which able to hydrolysis cellulosic feedstocks into monosaccharide was isolated from the horse manure. In this study, the complete genome of R. thermocellum M3 was sequencing and assembling. what’s more, the genome of R. thermocellum M3 was compared with the other R. thermocellum to reveale the mechanism of cellulosic saccharification by R. thermocellum M3. What’s more, predicted the key genes for elimination of feedback inhibition of cellobiose in R. thermocellum. The results indicated that the whole genome sequence of R. thermocellum M3 was consists of 3.6Mb chromosome with a 38.9% of GC%. To be specific, 8 Gene Island and 271 carbohydrate-active enzyme-encoded protein were detected. Additionally, the results of gene function annotation showed that 2071, 2120, and 1246 genes were annotated into COG, GO, and KEGG databases, respectively, and most of the genes were involved in carbohydrate metabolism and enzymatic catalysis. Different from other R. thermocellum, strain M3 has 3 proteins related to β-glucosidase, and the cellobiose hydrolysis was enhanced by the synergy of gene BglA and BglX. Meanwhile, the GH42 family, CBM36 family and AA8 family might participate in the cellobiose degrade.